The Parametrization of Universal Grammar. - Fanselow, Gisbert (Linguistik aktuell, 1993)
In this volume the subject of parametrization is addressed from various, though interrelated perspectives, ranging from learnability, the form and nature of parametrization, the role of the interface between morphology and syntax and the parameters of X-bar syntax, to the lexical parametrization hypothesis.